Analysis of correlated data with SAS and R - Shoukri, Mohamed M. (Chapman & Hall / CRC, 2007)
Discusses the methodologies used for the analysis of clustered and correlated data. This work includes a chapter devoted to the modeling and analyzing of normally distributed variables under clustered sampling designs. It offers an analysis of correlated count data that focuses on over-dispersion.